Educação profissional no Brasil do século XXI políticas, críticas e perspectivas - Vol. 1 - Filho, Domingos Leite Lima (Editora Oficina Universitária, 2021)
Structural unemployment and criminal management of the pandemic opened up the Brazilian tragedy. Hunger and misery, a drop in family income, difficulty finding a job are once again part of the barbaric daily life of the working class. If it is true that the professional education systems allow a better quality education for a portion of the working class, another portion attend public schools of poor quality, without minimum conditions for carrying out educational work. The chapters in this book seek to show the small achievements, limits and contradictions of the professional education policy, especially in the states of the Brazilian federation.